Generalized Production Functions - Zellner, A.; Revankar, N. S. (Review of Economic Studies, 1969)
Journal Article Generalized Production Functions Get access A. Zellner, A. Zellner University of Chicago Search for other works by this author on: Oxford Academic Google Scholar N. S. Revankar N. S. Revankar State University of New York at Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 2, April 1969, Pages 241–250, https://doi.org/10.2307/2296840 Published: 01 April 1969 Article history Received: 02 January 1967 Revision received: 07 October 1968 Published: 01 April 1969